Representasi Matematis dalam Pembelajaran dengan Model Problem-Based Learning Berbasis Etnomatematika Ditinjau dari Tipe Kepribadian - Sofri Rizka Amalia; Isnani Isnani (Universitas Hamzanwadi, 2019)
This research aims to describe the ability of students' mathematical representation in learning with ethnomatematics-based PBL models which is reviewed from personality type topology of Hippocrates and Galenus. This research is a qualitative descriptive reasearch. The subject of this reaserch is the fourth semester students of mathematics education study program. Subject collection using purposive sampling technique. Data collection techniques in this reaserch are observation, questionnaires, interviews, and documentation. Data validity uses triangulation.The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, drawing conclusions, and verifying conclusions. The results of this reaserchisthe choleric personality type does not fulfillthe first indicator is cannot use representation to model and interpret physical, social, and mathematical phenomena. Melancholy and phlegmatic personality typefulfill all indicators. Whereas the poetic type does not fulfill the third indicator, that is, it cannot choose, apply and translate between mathematical representations to solve problems.